Services for children with autism spectrum disorder in three, large urban school districts: Perspectives of parents and educators. (August 2015) - Iadarola, Suzannah; Hetherington, Susan; Clinton, Christopher; Dean, Michelle; Reisinger, Erica; Huynh, Linh; Locke, Jill; Conn, Kelly; Heinert, Sara; Kataoka, Sheryl; Harwood, Robin; Smith, Tristram; et al.
This study used qualitative methods to evaluate the perceptions of parents, educators, and school administrators in three large, urban school districts (Los Angeles, Philadelphia, and Rochester) regarding services for children with autism spectrum disorder within the context of limited district resources. Facilitators followed a standard discussion guide that contained open-ended questions regarding participants' views on strengths and limitations of existing services and contextual factors that would facilitate or inhibit the process of introducing new interventions. Three primary themes were identified: (1) tension between participant groups (teachers and paraprofessionals, staff and administration, teachers and parents, special education and general education teachers), (2) necessity of autism spectrum disorder–specific and behavioral training for school personnel, and (3) desire for a school culture of accepting difference. These themes highlight the importance of developing trainings that are feasible to deliver on a large scale, that focus on practical interventions, and that enhance communication and relationships of school personnel with one another and with families.